2021
DOI: 10.1111/myc.13395
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of deep tissue Candida invasion in neonates with invasive candidiasis

Abstract: Background Deep tissue Candida invasion represents a special entity among neonates with invasive candidiasis. We aimed to explore the risk factors and clinical outcomes for deep tissue Candida invasion among neonates with invasive candidiasis. Methods A retrospective data review of neonates admitted to NICU of Madinah maternity and children hospital, KSA from January 2012 to December 2019 was done. Data were analysed between infants with or without deep tissue candidiasis among infants with invasive candidiasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…The lower mortality rate indicates that, in comparison to the treatment provided in developed countries, our level of treatment still requires significant enhancement. A retrospective study Saudi Arabia showed that a total of 14 (11%) out of 130 neonates with IFI had EOD, and mortality rate was 35.7% in EOD group and 28.4% in NEOD group with IFI [18]. This is consistent with our finding, which showed that the mortality rate in EOD group was significantly higher than that in NEOD group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lower mortality rate indicates that, in comparison to the treatment provided in developed countries, our level of treatment still requires significant enhancement. A retrospective study Saudi Arabia showed that a total of 14 (11%) out of 130 neonates with IFI had EOD, and mortality rate was 35.7% in EOD group and 28.4% in NEOD group with IFI [18]. This is consistent with our finding, which showed that the mortality rate in EOD group was significantly higher than that in NEOD group.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we tried to see whether these risk factors for IFI, such as BW and GA, were also risk factors for EOD, but the results were not as expected. Hanin et al found that persistent Candida growth in blood cultures, prematurity and long-term antibiotic use are significant risk factors for EOD, which prolongs the length of hospital stay and increases the neonatal morbidity [18]. However, in the present study, no significant correlation was found between prematurity and EOD, suggesting that both premature or full-term infants with IFI should be alert to the possibility of EOD.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Among the public health issues caused by microbes, fungal diseases are relatively neglected, owing to the low mortality rate of 1.5% globally [1]. Fungal diseases, also known as mycoses, although acknowledged in the late 1980s, have now captured greater attention than ever before because of the escalating population of high-risk elderly individuals, immunosuppressed individuals, transplant recipients, and premature neonates [2][3][4][5][6][7]. The average life expectancy has increased tremendously with our current scientific knowledge and advancements in medical treatments increasing the population size of individuals over 65 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors for adult mortality with great representation across quantitative multivariate reports are concomitant bacteremia (Lee et al, 2020;Pieralli et al, 2021;Zhong et al, 2022;Gebremicael et al, 2023), high SOFA score (Bienvenu et al, 2020;Jung et al, 2020;Kutlu et al, 2022), presence of liver cirrhosis (González-Lara et al, 2017;Bartoletti et al, 2021;Battistolo et al, 2021;Meyahnwi et al, 2022), kidney dysfunction (Poissy et al, 2020;Mazzanti et al, 2021;Kutlu et al, 2022), and others summarized in Table 3 (Bassetti et al, 2020;Yoo et al, 2020;Kim et al, 2021). Particularly for early-age groups, additional risk factors for mortality include breakthrough candidemia , previous use of antibiotics for >2 weeks, persistent candidemia, and preterm gestation (<32 weeks; Eisi et al, 2022), placing the emphasis in the implementation and follow-up of protocols to properly manage neonatal care.…”
Section: Host Factorsmentioning
confidence: 99%